MY SAY: Will F1 go the way of foxhunting? - Abd Razak, Dzulkifli (2009)
When Malaysia announced that it wanted to be a more active player in Formula One (F1) by sponsoring, managing and developing its own team and machine, it was greeted with much excitement. Some lauded it as a bold move in the world of automotive engineering, and others for its multibillion advertising and promotional advantages. That it is a private sector’s initiative involving some of the most creative and successful entrepreneurs that the country has seen makes the proposition looks like a winning formula all round.